“Publication Impossible”: Breaking out of the Soft Science Mould. - Ting, Su Hie (Universitas Pelita Bangsa, Indonesia., 2020)
Researchers in the soft science disciplines often feel that they cannot publish like researchers in the sciences. Some may feel that they are into publishing books and conference papers, and not into writing journal papers. Others may feel that there are no high-impact journals in the soft sciences. These misconceptions are a glass ceiling that prevents researchers in the soft sciences from excelling in their publications and from adding to knowledge in the field. My “Publication Impossible” talk aims to inspire you to break out of the soft science mould. The first confine that needs to be broken down is the perception of “one person-one expertise area”. Research expertise is expandable through reading the literature and collaboration with researchers in other disciplines. Secondly, researchers in the soft sciences need to venture out of the comfort zone of familiar research methodologies. Exploration of how existing methods can be used in reformed ways allows transfer of methods across contexts and disciplines. This allows social phenomena to be seen through new lenses, thereby producing new insights in understanding human behaviour. The last confine to break is “self-censorship”, as in the limitations that researchers set on themselves. Researchers in the arts and humanities can aim high and succeed in publishing in impact factor journals. For this, a personal research culture cultivates growth into a full-fledged researcher with an international profile. Breaking out of the soft science mould in publication will impact the researcher’s profile, and push the frontiers of knowledge in the arts and humanities.